(untitled) (South East Asia Journal of Public Health, 2017)
Asia-Pacific countries are experiencing lifestyle-related non-communicable disease crises. Kimbe, one of Papua New Guineas provincial capitals is noted as the fastest growing city in the South Pacific subcontinent yet its impact on diabetes mellitus (DM) is not known. To determine pattern of newly diagnosed DM, we conducted a retrospective review of Kimbe General Hospital medical admissions from January 2009 to December 2012. 125 patients were diagnosed with diabetes with male: female ratio of 1.1: 1. Overall, number of patients diagnosed with DM at the hospital increased rapidly from 16 in 2009 to 49 in 2012; p <0.05. Majority of the patients were of young population aged <50 years representing 72 % of the cohort and predominantly of coastal province of origin. Almost 3/4th of the study population was based in Kimbe town and its suburb with only 32 subjects (25.6%) identified as rural residents; p<0.05. This study suggests that subjects living in Asia-Pacific area of rapid urbanization are at higher risk of diabetes compared to residents of rural areas. It highlights the need for adequate health planning and education as part of urbanization program in the DM-prone Asia-Pacific population. Further prospective studies are needed to verify our findings. South East Asia Journal of Public Health Vol.6(2) 2016: 48-52